A competence framework for artificial intelligence research. (4th July 2019) - Miracchi, Lisa
ABSTRACT: While over the last few decades AI research has largely focused on building tools and applications, recent technological developments have prompted a resurgence of interest in building a genuinely intelligent artificial agent – one that has a mind in the same sense that humans and animals do. In this paper, I offer a theoretical and methodological framework for this project of investigating "artificial minded intelligence" (AMI) that can help to unify existing approaches and provide new avenues for research. I first outline three desiderata that a framework for AMI research should satisfy. In Section 1, I further motivate the desiderata as well as the need for a new framework. Section 2 develops a general methodological approach, the "generative methodology, " and Section 3 develops a version of this methodology, the "Competence Framework for AI research" (CFAI).